FAULTING IN THE LITHOSPHERE: THE 35TH ANNIVERSARY OF THE IRKUTSK SCHOOL OF TECTONOPHYSICS - S. I. Sherman (Geodinamika i Tektonofizika, 2015)
The history of tectonophysical studies in Irkutsk began in the 1950s at the initiative of Prof. V.N. Danilovich. Tectonophysics as a new scientific field in geology was enthusiastically supported by research institutes of the actively developing Siberian Branch of the USSR Academy of Sciences, including the Institute of the Earth's Crust (IEC). In late 1950s, V.N. Danilovich, G.V. Charushin, O.V. Pavlov, P.M. Khrenov, S.I. Sherman and other scientists began to conduct large-scale studies of faults and rock fracturing with application of methods of structural analysis of fault tectonics and taking into account types of physical and mechanical destruction of the crust. In 1979, the IEC Scientific Council reviewed the initiative of Prof. S.I. Sherman, who was supported by Academician N.A. Logachev and Doctor of Geology and Mineralogy O.V. Pavlov, and approved the decision to establish the Laboratory of Tectonophysics, that has been and is the only scientific research team of the kind in the territory of Russia eastward of the Urals and, in fact, the second in the Russian Federation. Its studies are based on concepts dealing with physical regularities of crustal faulting that are described in the monograph published by S.I. Sherman [Sherman, 1977], three co-authored volumes of Faulting in the Lithosphere [Sherman et al., 1991, 1992, 1994] and other scientific papers. These publications have consolidated results of studies conducted by the team of researchers from the Laboratory, which can be called the Irkutsk school of tectonophysics. On the eve of the 21st century, the Laboratory successfully extended application of physics of destruction of materials and mathematical methods of analysis to studies of structural patterns of faults varying in ranks in the crust and the upper lithosphere.We conducted comprehensive studies of tectonophysical regularities of formation of large crustal faults, pioneered in establishing quantitative relationships between main parameters of faults, i.e. length and depth, length and amplitude of displacement, length and density, and estimated the factors determining such parameters. A model showing the fault structure was proposed with account of changes of physical properties of the crust with depth. It was shown that faulting in the crust follows the laws of deformation and destruction of Maxwell body.With accumulation of the knowledge on regularities of faulting in the lithosphere, analyses the state of stresses in the lithosphere has become prioritised, and this is one of the top challenges in geodynamics and tectonophysics. Tectonophysics from Irkutsk published the first map of the state of stresses of the Baikal rift zone and proposed new concepts for studying crustal stresses by structural geological methods. Based on such concepts, a new map of the state of stresses of the upper lithosphere was constructed.Studies of faulting included researches of areas around virtual axes of faults and variations of sizes of such areas, and a concept of an area of dynamic influence of large lithospheric faults was proposed. It is established that internal patterns of areas of dynamic influence of faults are composed of zones that can be revealed both laterally and in depth, and such zonal patterns depend on the degree of tectonical and dynamo-metamorphical transformation of the rocks.The internal structure of continental fault zones was studied, and three main disjunctive stages were revealed, each corresponding to a specific type of deformation behaviour of the medium, its state of stresses, pathogenesis of faults varying in ranks, and variations of parameters in space and time.Triple paragenesises of fractures were revealed and analysed for a number of regions, and such studies provided the basis to propose a method of specialized mapping of the crust, which provides for determination of locations of fault zones and their boundaries, conditions of their formation and major specific features of their internal structures. This method can be effectively applied within the framework of conventional geological surveys of any scale.Results of studies of tectonic divisibility of the Earth based on advanced tectonophysical concepts were referred to establish the zone-block structure (ZBS) of the lithosphere. Analyses of faults at various scales showed a strict hierarchy of ranks in the ZBS of the lithosphere in Central Asia, and actual characteristics of 11 hierarchic levels (from global to local) were revealed and described in quantitative terms. With reference to the ZBS concept, the Baikal rift was studied, and the soil radon concentration pattern of Pribaikalie was analysed and its main spatial and temporal regularities were revealed.Comprehensive geological, structural, tectonophysical and geoelectrical studies were conducted in the Cenozoic and Mesozoic basins of Pribaikalie and Transbaikalie, and results were consolidated and published. The fault-block patterns, the deep structure, the state of stresses and seismicity of the crust were studied in a number of areas in the region.Complex tectonophysical studies were initiated in the Yakutian diamond-bearing province to reveal structural factors that control the kimberlite locations, and the first results were reported. By applying tectonophysical methods, it was established that periods of formation of kimberlite bodies are related to stages of formation and activation of the fault pattern of the platform cover. A pioneering conclusion was stated that in the structural control over kimberlite magmatism of the Siberian platform, the dominant role is played by fault zones of the orthogonal network, which were activated in the regime of alternating-sign displacements at different stages of the platform's development in the Paleozoic and Mesozoic.Physical modelling experiments using an original installation were conducted, and, among its main achievements, an important result is modelling of the process of formation of the Baikal rift zone (BRZ) by an elasto-plastic model in conformity with criteria of similarity. The Shanxi rift system was also modelled, and its physical modelling study was conducted jointly with scientists from China under the Russian-Chinese project supported by the Russian Foundation for Basic Research.Besides, the article informs about commencement of original experimental studies of deformation waves in elasto-plastic mediums and describes objectives of tectonophysical studies for the nearest future.